IMPLEMENTASI PENGANGGARAN BERBASIS KINERJA DAN KOMPETENSI TERHADAP AKUNTABILITAS PEMERINTAHAN DAERAH KABUPATEN MUNA BARAT - Wa Ode Sartika Tika; Rasmin; Ahmad Ridwan; Harpiang wardingsih; Muhammad Taslim; Fatma Aprilia Ningsih (Halu Oleo University, 2025)
The purpose of this study is to test and explain the influence of performance-based budgeting and competency on the accountability of the West Muna Regency Government. The approach to this study is to use a quantitative approach with a postpositivist paradigm. Data collection was carried out cross-sectionally using a questionnaire. The population of this study was all SKPD employees involved in regional financial management in the West Muna Regency Government in 40 Regional Work Units (SKPD) with a total of 120 employees. The sample size of this study was determined by the census method, so the sample size was 120 people. The analysis tool used for hypothesis testing is Partial Least Squares (PLS). The results of the study indicate that performance-based budgeting has a significant positive effect on government accountability in the West Muna Regency SKPD, and competency has a significant positive effect on government accountability in the West Muna Regency SKPD.